2020
DOI: 10.1371/journal.pone.0231309
|View full text |Cite
|
Sign up to set email alerts
|

Physical influences on seafarers are different during their voyage episodes of port stay, river passage and sea passage: A maritime field study

Abstract: Introduction During a sea voyage, crew members of vessels are permanently exposed to physical stress caused by noise, vibration and heat. This study aims to describe the extent of the physical influences on board container ships and the resulting stress. Methods Up to four scientific investigators accompanied six sea voyages on container ships under German management. Workplace and person-related measurements for noise, vibration and climatic parameters were carried out on the vessels during the three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The estimated average noise intensity during working hours was at almost 85 dB. This value follows findings obtained by Oldenburg et al [ 11 ] and measured by Mansi et al [ 14 ]. They are, obviously, insufficiently protected as they use noise protection agents only occasionally.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The estimated average noise intensity during working hours was at almost 85 dB. This value follows findings obtained by Oldenburg et al [ 11 ] and measured by Mansi et al [ 14 ]. They are, obviously, insufficiently protected as they use noise protection agents only occasionally.…”
Section: Discussionsupporting
confidence: 89%
“…However, ship noise onboard can endanger seafarers and passengers, while underwater and airborne emitted ship noise can affect port areas and coastal residents, even the fauna on maritime routes [ 10 ]. Based on the research of [ 11 , 12 , 13 , 14 ], the principal source of noise on board can be assumed to be the engine room, where the highest levels of intensity can be found. On most ships, noise levels over 100 dB(A) are present, reach the levels of 110 dB(A) in the noisier area and decrease depending on the location on board.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Oldenburg [12] does not include noise as the cause of hypertension in sailors. However, the same author has recently shown that engine room personnel remain exposed to harmful noise levels, greater than 85 dB (A) [13].…”
mentioning
confidence: 99%
“…It should suggest that technological advances on noise exposure prevention on board ships are significant for 40 years (improvement of the insulation of living areas, automation of machines, soundproofed surveillance rooms, diesel-electric propulsion...) and therefore that seamen are today less exposed. L E T T E R T O T H E E D I T O R still exposed to harmful noise levels, above 85 dB (A), even today [11][12][13]. Turan et al [14] consider that ships easily meet the International Maritime Organisation criteria, while people working on board such ships are still likely exposed to high noise levels [14].…”
mentioning
confidence: 99%